Validitas dan Praktikalitas Modul Sistem Koloid Berorientasi Chemo-Entrepreneurship (CEP) untuk Kelas XI IPA SMA atau MA - Maifil Dwi Andrean; Yerimadesi Yerimadesi; Fauzana Gazali (Universitas Negeri Padang, 2019)
One effort that can be done to prepare SMA or MA students in entering the world of work is equipping them with the entrepreneurship skills, namely by integrating entrepreneurship into chemistry subjects through teaching materials in the form of modules. This study aims to reveal the level of validity and practicality of a CEP-oriented colloidal system module developed for class XI SMA or MA. The type of research used is Research and Development with 4-D model (define, design, develop, and disseminate). The research instrument used was a questionnaire in the form of validity and practicality sheet. This module was validated by 3 UNP chemistry lectures and 2 chemistry teachers of SMAN 12 Padang. Practicality test were conducted on 2 chemistry teachers and 30 eleventh grade students of SMAN 12 Padang. Data was analyzed by Cohen Kappa Formula. The results of the validity test showed that the module has a very high validity category (kappa = 0.86). Practicality test results by teachers and students showed that the module has very high practicality category (kappa = 0.82 and 0.83). Based on the results of this research, it can be concluded that the module developed was valid, practical.